9(x-2)+5=-13

Simple and best practice solution for 9(x-2)+5=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-2)+5=-13 equation:


Simplifying
9(x + -2) + 5 = -13

Reorder the terms:
9(-2 + x) + 5 = -13
(-2 * 9 + x * 9) + 5 = -13
(-18 + 9x) + 5 = -13

Reorder the terms:
-18 + 5 + 9x = -13

Combine like terms: -18 + 5 = -13
-13 + 9x = -13

Add '13' to each side of the equation.
-13 + 13 + 9x = -13 + 13

Combine like terms: -13 + 13 = 0
0 + 9x = -13 + 13
9x = -13 + 13

Combine like terms: -13 + 13 = 0
9x = 0

Solving
9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '9'.
x = 0

Simplifying
x = 0

See similar equations:

| (x+6)(x^3-3x+5)= | | 2x=16/9 | | x^2+y^2-6/5x+9/25-9=0 | | 6a+12=2a+-16 | | -4(7)+2(-9)-7(-9)=z | | 3*4/5 | | (x-4)(x^2-7x+2)= | | m+3m+4m+4= | | 2/6*3/4 | | 44-5h=6h | | X=20+-0.4y+-0.02z | | 9x-3(x-8)=6(x-3)+6 | | 20000(.06x+.07y)=1300 | | 9x-3(x-8)=6x-24 | | 13q-2=-28 | | 6-2x=4(2-3x)+8x | | 9=-2m+-1 | | .93x+.97(4-x)=3.8 | | 2(x-4)-x=3 | | (3x-3)(3x-8)= | | 1+8(-4n-2)=-39-8n | | -2/3r+2r=6/5r+12/5 | | (4x^2+1)(6x^2+7)= | | 5x-6-2x=4x+8 | | 6x+6=6x-9 | | 2/3(6x+9)=18 | | -8v=-80 | | -2(-x-8)=2x+15 | | -3(x-5)+12x=9(x+2)+12 | | 60+15=4 | | d-16=-50 | | 2(6w+8)=2(4w+24) |

Equations solver categories